Irish setter dogs affected with rod/cone dysplasia contain a nonsense mutation in the rod cGMP phosphodiesterase beta-subunit gene. - Suber, M L (1993)
Irish setter dogs affected with a rod/cone dysplasia (locus designation, rcd1) display markedly elevated levels of retinal cGMP during postnatal development. The photoreceptor degeneration commences approximately 25 days after birth and culminates at about 1 year when the population of rods and cones is depleted. A histone-sensitive retinal cGMP phosphodiesterase (PDE; EC 3.1.4.35) activity, a marker for photoreceptor PDEs, was shown previously to be present in retinal homogenates of immature, affected Irish setters. Here we report that, as judged by HPLC separation, this activity originates exclusively from cone photoreceptors, whereas rod PDE activity is absent. An immunoreactive product the size of the PDE alpha subunit, but none the size of the beta subunit, can be detected on immunoblots of retinal extracts of affected dogs, suggesting a null mutation in the PDE beta-subunit gene. Using PCR amplification of Irish setter retinal cDNA, we determined the complete coding sequence of the PDE beta subunit in heterozygous and affected animals. The affected PDE beta-subunit mRNA contained a nonsense amber mutation at codon 807 (a G-->A transition converting TGG to TAG), which was confirmed to be present in putative exon 21 of the affected beta-subunit gene. The premature stop codon truncates the beta subunit by 49 residues, thus removing the C-terminal domain that is required for posttranslational processing and membrane association. These results suggest that the rcd1 gene encodes the rod photoreceptor PDE beta subunit and that a nonsense mutation in this gene is responsible for the production of a nonfunctional rod PDE and the photoreceptor degeneration in the rcd1/rcd1 Irish setter dogs.